The Prospects of Structured Products in Malaysia - Ng, Siew Ping (2008)
Structured products have caught the limelight in the financial markets in Asia in the past few years. Although the demand for structured investment products in Malaysia is still at the infancy stage as reflected in the size and type of assets involved in the transactions, but many banks in Malaysia are already preparing to roll out such products to meet their customers' growing appetite for alternative asset classes that offer good returns. The Malaysia’s structured products market is fast expanding as issuances multiply and increase in size in recent years. However, the spikes in the global financial markets caused by the derivatives trading-related scandals unfolded over the years and the current subprime mortgage crisis are likely to raise investor fears on structured products. In view of the (i) queasy consequences of the credit market turmoil; as well as (ii) the structured product-related financial scandals that have unfolded over the years and to the best knowledge of the author, there were no researches or studies done thus far that tried to analyse the non-financial market impact of the past financial crises related to structured products on the Malaysian capital market, and hence, this has motivated the author to perform this study to ascertain the painful lessons that can be learnt from these past structured products-related crises and the current financial turbulence as well as how Malaysia can move forward in this front? Thus, this study attempts to fill these gaps by firstly investigating the current concerns or issues related to structured products that are being encountered by various capital market stakeholders in Malaysia; secondly, establishing the nonfinancial risks associated with structured products supported by the relevant case studies and outlining the lessons learnt; thirdly, discussing the potential future challenges of structured products and substantiating whether it is the right move for Malaysia to continue to develop and open up its capital market further in the midst of the current financial meltdown; and finally, recommending ways that are possible to help Malaysia to strengthen its structured products market. This study shows that the future of structured products is bright as higher take up rate of such products from potential investors can be expected with further regulatory liberalization. However, the capital market stakeholders have to be extremely mindful of the risks that these products are capable in inflicting as evidenced in the current and past financial events. Hence, going forward, it is prudent for the regulators to further broaden and deepen the structured products market by progressively liberalizing the regulations but they have to implement tighter control measures and continue to supervise these structured product activities in order to ensure that the investors’ interest is protected. However, this comes with a condition that if all the challenges and weaknesses that have been identified in Chapter 4 are being addressed and overcome.